Acceptor dependent catalytic properties of GH57 4-α-glucanotransferase from Pyrococcus sp. ST04 - Jung, Jong-Hyun; Hong, Seungpyo; Jeon, Eun Jung; Kim, Min-Kyu; Seo, Dong-Ho; Woo, Eui-Jeon; Holden, James F.; Park, Cheon-Seok (Frontiers in Microbiology, 2022)
The 4-α-glucanotransferase (4-α-GTase or amylomaltase) is an essential enzyme in maltodextrin metabolism. Generally, most bacterial 4-α-GTase are classified into glycoside hydrolase (GH) family 77. However, hyperthermophiles have unique 4-α-GTases belonging to GH family 57. These enzymes are the main amylolytic protein in hyperthermophiles, but their mode of action in maltooligosaccharide utilization is poorly understood. In the present study, we investigated the catalytic properties of 4-α-GTase from the hyperthermophile Pyrococcus sp. ST04 (PSGT) in the presence of maltooligosaccharides of various lengths. Unlike 4-α-GTases in GH family 77, GH family 57 PSGT produced maltotriose in the early stage of reaction and preferred maltose and maltotriose over glucose as the acceptor. The kinetic analysis showed that maltotriose had the lowest KM value, which increased amylose degradation activity by 18.3-fold. Structural models of PSGT based on molecular dynamic simulation revealed two aromatic amino acids interacting with the substrate at the +2 and +3 binding sites, and the mutational study demonstrated they play a critical role in maltotriose binding. These results clarify the mode of action in carbohydrate utilization and explain acceptor binding mechanism of GH57 family 4-α-GTases in hyperthermophilic archaea.